Site, hybrid crosses and clone effect on growth and wood properties of Populus - Monteoliva, S.; Senisterra, G. (Forest Systems, 2008)
The objective of this paper was to study site, hybrid cross and clone effects on total height, BHD [Breast height diameter], volume, wood basic density, fibre length and yield, of eleven poplars clones. 10-year-old hybrid poplar clones were sampled at two sites in Argentina (MD and EG). The material studied consisted of two poplar hybrid crosses Populus deltoides x P. deltoides and P. deltoides x P. nigra (P. x canadensis = P. x euramericana), as well as P. deltoides. Sites influenced significantly growth traits and wood density, hybrid influenced tree height, wood density and fibre length and clones influenced all variables. MD trees were 5% higher and 2% denser than EG trees, but EG trees were 7% greater in BDH and 11% more volume than the MD trees. P. deltoides and P. deltoides intra specific crosses were 4% higher and 4% denser than P. x canadensis trees. P. x canadensis fibre length was 3% higher than P. x deltoides. According to all properties, difference between site and hybrid were not very importanThe properties of the clones had different responses regardless of the hybrid crosses. 610-31 and 564-17 clones (P. x deltoides) and 568-1 and Triplo (P. x canadensis) clones were distinguished.